Implementation of biological active compound BIO-AP-IRGA: chemical features of enriched yogurt and cottage cheese - Sagandyk, Assem; Makangali, Kadyrzhan; Zhakupova, Gulmira; Tultabayeva, Tamara; Tokysheva, Gulzhan (Eastern-European Journal of Enterprise Technologies, 2024)
The imbalance of micro- and macronutrients is a significant health issue, often due to poor nutrition, vitamin deficiencies, and disruptions in mineral metabolism. To address these challenges, biologically active supplements (BASs) are gaining popularity. In Kazakhstan, the BIO-AP-IRGA dietary supplement, derived from dried saskatoon berry, chokeberry, and whey, was developed to improve local food products. The study explored integrating BIO-AP-IRGA into yogurt and cottage cheese, assessing the impact on their nutritional and chemical properties. Standard analytical methods were used to evaluate the fortified products. The results showed that the addition of BIO-AP-IRGA significantly increased the carbohydrate content, nearly doubling it in yogurt and increasing it by eight times in cottage cheese. Additionally, the polyphenol content increased in both yogurt and cottage cheese; yogurt showed a slight increase, while cottage cheese saw nearly a twofold rise. However, the amino acid content decreased with the increasing amount of BIO-AP-IRGA, showing an inverse relationship. These findings highlight the physicochemical changes that occur when BIO-AP-IRGA is incorporated into dairy products. The supplementation improves the nutritional quality of yogurt and cottage cheese, particularly by enhancing polyphenol and vitamin C levels. This innovation presents an opportunity for the food industry to develop functional dairy products with potential health benefits, addressing nutrient deficiencies and promoting better health